Efforts toward PET-Activatable Red-Shifted Silicon Rhodamines and Silicon Pyronine Dyes - Carsten Sven Kramer; Thines Kanagasundaram; Jessica Matthias; Klaus Kopka (MDPI AG, 2023)
Tracers for bimodal optical imaging and positron emission tomography unite multiple advantages in a single molecule. Their tumor-specific uptake can be visualized after their PET activation by radiofluorination via PET/CT or PET/MRI allowing for staging or therapy planning, while their non-radioactive moiety additionally facilitates the visualization of malignant tissue during intraoperative fluorescence-guided surgery or in histological assessments. The silicon-bridged xanthene core offers the opportunity for radiofluorination with SiFA isotope exchange to obtain a small-molecule, PET-activatable NIR dye that can be linked to different target vectors. Herein, we demonstrate for the first time the PET-activation of a fluorinated silicon pyronine, belonging to a class of low-molecular-weight fluorescence dyes with a large Stokes shift (up to 129 nm) and solvent-dependent NIR dye properties, with a successful radiochemical conversion of 70%. The non-fluorinated pyronine precursor is easily accessible by a three-step sequence from commercially starting material with a 12% overall yield. Moreover, a library of seven unusually functionalized (by approximately 15 nm), red-shifted silicon rhodamines were synthesized in three- to four-step sequences and the optical properties of the novel dyes were characterized. It was also shown that the synthesized silicon rhodamine dyes can be easily conjugated by amide bond formation or 'click-reaction' approaches.